To find the product of \((2q^9 + 3q^7)(-6q^2 + 9)\), we will use the distributive property (also known as the FOIL method for binomials).
-
Distribute \(2q^9\) to both terms in the second factor:
- \(2q^9 \cdot (-6q^2) = -12q^{11}\)
- \(2q^9 \cdot 9 = 18q^9\)
-
Distribute \(3q^7\) to both terms in the second factor:
- \(3q^7 \cdot (-6q^2) = -18q^9\)
- \(3q^7 \cdot 9 = 27q^7\)
-
Now, add all these results together: \[ -12q^{11} + 18q^9 - 18q^9 + 27q^7 \]
-
Combine like terms: \[ -12q^{11} + (18q^9 - 18q^9) + 27q^7 = -12q^{11} + 0 + 27q^7 = -12q^{11} + 27q^7 \]
The final result is: \[ -12q^{11} + 27q^7 \]
The correct response is: −12q11+27q7